Smaki i zapachy dzieciństwa z perspektywy językowo-kulturowej (na podstawie wybranych polskich blogów kulinarnych) - Jóźwiak, Natalia (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2020)
The article attempts to reconstruct the linguistic and cultural image of childhood tastes in selected culinary blogs. The reconstruction is based on entries referring to two dishes most frequently mentioned in the context of childhood: broth and apple pie.